Determinan Asumsi Going Concern dalam Pemberian Opini Audit - Muhammad Yusuf; Muhammad Irfan Tarmizi; Maryati Maryati (Jurnal Akuntansi dan Governance, 2023)
Objectives. To analyze the effect of cash flow, audit quality, and audit risk on the going concern assumption in giving audit opinion.Design/method/approach. This is a quantitative study with secondary data in the form of published financial reports. The population consists of property and real estate sector companies listed on the Indonesia Stock Exchange (IDX) during the 2016-2020 period using purposive sampling. The selected sample is 43 companies with a total of 215 observations of the data and analyzed with Logistic regression analysis.Results/findings. The results show that cash flow has no significant negative effect, audit quality has no significant positive effect, and audit risk has a significant positive effect on the going concern assumption in giving audit opinion.Theoretical contribution. Academics can make additional references regarding the determinants of the going concern assumption in audit literature.Practical contribution. Auditors can use the current ratio as one of the audit risk factors in determining going concern assumption, the management committee can maximize the company's financial management so as not to accept the going concern assumption, owners and investors can pay attention and periodically evaluate all financial aspects to assess performance managementLimitations. This study has several limitation, such as limited number of independent variables; a limited sample of property and real estate sector companies listed on the IDX; and the observed data is limited to 2016-2020.